Physical properties of aqueous suspensions of goethite (alpha-FeOOH) nanorods – Part I: In the isotropic phase - Lemaire, B.J.; Davidson, P.; Ferré, J.; Jamet, J.P.; Petermann, D.; Panine, P.; Dozov, I.; Jolivet, J.P. (European Physical Journal E, 2004)
Depending on volume fraction, aqueous suspensions of goethite (alpha-FeOOH) nanorods form a liquid-crystalline nematic phase (above 8.5%) or an isotropic liquid phase (below 5.5%). In this article, we investigate by small-angle X-ray scattering, magneto-optics, and magnetometry the influence of a magnetic field on the isotropic phase. After a brief description of the synthesis and characterisation of the goethite nanorod suspensions, we show that the disordered phase becomes very anisotropic under a magnetic field that aligns the particles. Moreover, we observe that the nanorods align parallel to a small field (< 350 mT), but realign perpendicular to a large enough field (> 350 mT). This phenomenon is interpreted as due to the competition between the influence of the nanorod permanent magnetic moment and a negative anisotropy of magnetic susceptibility. Our interpretation is supported by the behaviour of the suspensions in an alternating magnetic field. Finally, we propose a model that explains all experimental observations in a consistent way.